Small RNA sequencing of pectoral muscle tissue reveals microRNA‐mediated gene modulation in chicken muscle growth. Issue 3 (20th January 2020) - Zhang, Zengrong; Qiu, Mohan; Du, Huarui; Li, Qingyun; Gan, Wu; Xiong, Xia; Yu, Chunlin; Peng, Han; Xia, Bo; Song, Xiaoyan; Yang, Li; Hu, Chenming; et al.
Abstract: Sichuan mountainous black‐bone (SMB) chicken is a small‐sized black‐feathered chicken breed with low amount of meat, while Dahen (DH) chicken has a larger body size and a faster growth rate. MicroRNAs (miRNAs) are involved in various physiological processes, but their role in chicken muscle growth remains unclear. We aimed to investigate the miRNAs and pathways participating in the muscle growth of chicken. MiRNA profiles of four SMB chickens and four DH chickens were detected by small RNA sequencing. A total of 994 known miRNAs were identified, among which gga‐miR‐1a‐3p, gga‐miR‐148‐3p and gga‐miR‐133a‐3p exhibited the highest enrichment in both breeds of chickens. Thirty‐two miRNAs were differently expressed between SMB and DH chickens. The differently expressed miRNAs were mainly associated with fatty acid metabolism, immunity and MAPK activation‐related processes. Kyoto encyclopaedia of genes and genomes (KEGG) analysis showed that miRNAs were involved in the immunity‐related and MAPK signalling pathways. Moreover, miR‐204 was downregulated in DH chicken compared with SMB chicken, and significantly inhibited the expression of MAP3K13, which is involved in the MAPK pathway. It was confirmed through luciferase reporter assays that miR‐204 specifically inhibited the activity of MAP3K13. Our results helped demonstrate the potential molecular mechanisms of muscle growth in chickens and provide valuable information for chicken breeding.